2015
DOI: 10.2217/nnm.14.134
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Stimulation of Osteoblastogenesis from Mesenchymal Stem Cells: Nanotopography and Nanokicking

Abstract: In the future it is envisaged that this technology may have beneficial therapeutic applications in the healthcare industry, for conditions whose overall phenotype maybe characterized by weak or damaged bones (e.g., osteoporosis and bone fractures), and which can benefit from having an increased number of osteoblastic cells in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Since we know the surface area of the cantilever tip (10 µm radius) we can estimate that a cuboidal cell of 140 × 100 µm would receive a peak force of 17 nN due to this vibration (9 nm, 1 kHz). It is worth noting that this measurement is largely consistent with our previously calculated estimates in the 10s of nN for vibration of 30 nm at 1 kHz [20][21][22]40 .…”
Section: Afm Measurements Of Collagen Gel During Nanovibrationsupporting
confidence: 91%
See 2 more Smart Citations
“…Since we know the surface area of the cantilever tip (10 µm radius) we can estimate that a cuboidal cell of 140 × 100 µm would receive a peak force of 17 nN due to this vibration (9 nm, 1 kHz). It is worth noting that this measurement is largely consistent with our previously calculated estimates in the 10s of nN for vibration of 30 nm at 1 kHz [20][21][22]40 .…”
Section: Afm Measurements Of Collagen Gel During Nanovibrationsupporting
confidence: 91%
“…These factors are important when using nanoscale amplitudes as consistent vibration ensures that all cells on the bioreactor experience the same levels of acceleration. Previous experiments [19][20][21][22][23] used vibration amplitudes of 15 -35 nm and frequencies of 1 Hz -5 kHz and the most significant osteogenic effects were observed at 1 kHz 20,22 . It is important that the bioreactor operates within this frequency range and crucial that this range is well below the bioreactor's resonant condition to avoid resonant amplification/damping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously used nanoscale vibrational displacements to stimulate osteogenesis in MSCs cultured on tissue culture plastic in 2D 17,18 . This work identified that mechanical stimulation of 1000 Hz frequency with 15-nm vertical displacement promoted MSC differentiation 18 .…”
mentioning
confidence: 99%
“…In this sense, many studies have demonstrated that diverse cellular signaling cascades become activated as a consequence of mechanical stimulation, a process known as mechanotransduction (see [12,13] for reviews). Examples of these mechanical stimulations include matrix-elasticity modifications, substrate nanotopography patterns [14,15], local nanoforces (internal or external to the cell) [16,17], and nanovibrations [18][19][20][21][22]. Cells react effectively to such mechanical alterations by inducing cellular responses.…”
Section: Introductionmentioning
confidence: 99%